ANALISIS FUNDAMENTAL KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 - Qisthinanda, Nurshadrina (Jurnal KIAFE, 2021)
This study aims to obtain empirical evidence of the effect of the Current Ratio, Debt to Equity Ratio, Net Profit Margin, Price to Book Value on stock returns of infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. Data analysis was carried out using Descriptive Statistical Analysis, Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis Testing, and Determinant Coefficients using SPSS 25 tools. Meanwhile, Net Profit Margin and Price to Book Value have no significant and positive effect on stock returns.